Faktor-faktor yang mempengaruhi kejadian obesitas pada remaja - Weni Kurdanti; Isti Suryani; Nurul Huda Syamsiatun; Listiana Purnaning Siwi; Mahardika Marta Adityanti; Diana Mustikaningsih; Kurnia Isnaini Sholihah (Jurnal Gizi Klinik Indonesia, 2015)
Background: The cause of obesity in adolescents is multifactorial. Increased consumption of fast food (fast food), lack of physical activity, genetic factors, the influence of advertising, psychological factors, socioeconomic status, diet, age, and gender are all factors that contribute to changes in energy balance and lead to obesity.Objective: To determine the factors that affect the incidence of obesity in adolescents. Method: A case-control study with a total of 144 subjects, cases are obese adolescents (BMI/U> + 2SD) and controls were non-obese adolescents. The independent variable is the macronutrient intake, fiber intake, the pattern of consumption of fast food, the consumption patterns of food / sugary beverages, physical activity, psychological factors (self-esteem), genetic factors, and intake of breakfast, while the dependent variable was the incidence of obesity. Data analysis using chi-square test and logistic regression. Results: Factors significantly associated (p<0.05) and a risk factor for obesity in adolescent is energy intake (OR=4.69; CI 95%=2.12-10.35); fat (OR=2.34; CI 95%=1.19-4.57); carbohydrates (OR=2.64; CI 95%=1.34-5.20); the frequency of fast food (OR=2.47; CI 95%=1.26-4.83); and the morning breakfast intake (OR=5.24; CI 95%=2.56-10.71). Conclusion: Teens who have excessive macronutrient intake, the frequency of consumption of fast food often, physical activity is not active, has a mom and dad with obesity status, and no breakfast, greater risk of obesity.